A Community of Practice Approach to Improving Gender Equality in Research - Palmén, Rachel; Müller, Jörg (Routledge Research in Gender and Society, 2023)
Bringing together the latest research among various communities of practice (disciplinary and place based as well as thematically organised), this volume reflects upon the knowledge, experience and practice gained through taking a unique community of practice approach to fostering gender equality in the sectors of research and innovation, and higher education in Europe and beyond. Based on research funded by the European Union, it considers how inter-organisational collaboration can foster change for gender equality through sharing of experiences of Gender Equality Plan implementation and examining the role of measures such as change-monitoring systems. As such, it will appeal to social scientists with interests in organisational change, the sociology of work and gender equality.